1992
DOI: 10.1159/000118897
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Double-Blind Study of Three Different Doses of the New cAMP-Phosphodiesterase Inhibitor Rolipram in Patients with Major Depressive Disorder

Abstract: A multicenter randomized 4-week interindividual double-blind study was carried out in 58 hospitalized patients with major depressive disorder (DSM III 296.23,296.22,296.33,296.32,296.53 and 296.52) to test the dose-effect relationship of three different doses of the new cAMP-phosphodiesterase inhibitor rolipram: 3 × 0.25 mg, 3 × 0.50 mg and 3 × 1.00 mg rolipram/day. With respect to the desired effect, the 3 × 0.50 mg dosage stood out from the others in almost all relevant parameters. With respect to the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(58 citation statements)
references
References 4 publications
3
55
0
Order By: Relevance
“…A PDE4-specific inhibitor rolipram has antidepressant effects on animals and patients with major depression. [61][62][63] PDE4D knockout mice show antidepressant-like behavior, which is further increased by the antidepressants desipramine and fluoxetine but not by rolipram. This suggests that the PDE4D subtype is an essential mediator of the antidepressant effects of rolipram.…”
Section: Discussionmentioning
confidence: 99%
“…A PDE4-specific inhibitor rolipram has antidepressant effects on animals and patients with major depression. [61][62][63] PDE4D knockout mice show antidepressant-like behavior, which is further increased by the antidepressants desipramine and fluoxetine but not by rolipram. This suggests that the PDE4D subtype is an essential mediator of the antidepressant effects of rolipram.…”
Section: Discussionmentioning
confidence: 99%
“…Through cAMP-mediated mechanisms, pharmacotherapy that inhibits PDE4 is prone to increase the transcription and function (Miller, Vogt et al 2002;Pace, Hu et al 2007) of reduced numbers of FX dendritic glucocorticoid receptors (Miyashiro, Beckel-Mitchener et al 2003) involved in hypothalamic-pituitaryadrenal (HPA) regulation (Hessl, Rivera et al 2004). A clinical trial of rolipram reported acceptable tolerance levels at clinically relevant doses (Fleischhacker, Hinterhuber et al 1992). In clinical and preclinical trials, the main human PDE4 inhibitor side effect, thought to be due to PDE4D activity (Robichaud, Savoie et al 2002;Robichaud, Stamatiou et al 2002;Conti, Richter et al 2003), is emesis at clinical doses while rats are more susceptible to toxic effects like arteriopathy.…”
Section: Camp Therapymentioning
confidence: 99%
“…In the 1980s and early 1990s, a number of open (Zeller et al 1984) and controlled clinical trials (Bertolino et al 1988;Bobon et al 1988;Fleischhacker et al 1992;Hebenstreit et al 1989) demonstrated that rolipram, a specific inhibitor of the high-affinity cAMP PDE4, may have antidepressant efficacy in depressed patients. In addition, there is evidence that rolipram may have a faster onset of response compared with the standard antidepressants.…”
Section: Strategies To Potentiate the Creb/bdnf/ Bcl-2 Cascade For Thmentioning
confidence: 99%